Developing the flipped learning instrument in an ESL context: The experts’ perspective - Wahyu Hidayat; Mohammad Musab bin Azmat Ali; Nur Asmawati Lawahid; Mujahidah Mujahidah (Jurnal Penelitian dan Evaluasi Pendidikan, 2021)
Numerous studies have accepted the flipped learning approach as an approach in implementing technological-based classroom environments. This article aims to identify the required constructs in developing an instrument for flipped learning in an ESL environment. This study uses the Fuzzy Delphi method to collect and analyze the viewpoints of 18 experts from relevant fields. An online questionnaire was developed to gather the experts’ agreement towards seven constructs: flexible environments, the shift in learning culture, intentional content, progressive networking activities, professional educators, engaging effective learning experiences, and diversified seamless learning platforms, and 68 items gathered from the literature. The Fuzzy Delphi Method (FDM) analysis rejected seven items, finalizing the instrument with seven constructs and 61 items. The instrument is beneficial to teachers and learners of ESL and developers of technology-based learning methods. The implication of the study is the provision of the constructs to help guide and implement the flipped learning approach in educational contexts. Furthermore, these constructs can be used as the basis for further investigations that lead to developing frameworks or models for the flipped learning approach. Future works on the topic may look at a bigger sample for stronger results. Furthermore, the instrument developed can be used on the student population and in other contexts as well.